Genome-wide detection of genotype environment interactions for flowering time in Brassica napus - Han, Xu; Tang, Qingqing; Xu, Liping; Guan, Zhilin; Tu, Jinxing; Yi, Bin; Liu, Kede; Yao, Xuan; Lu, Shaoping; Guo, Liang (Frontiers in Plant Science, 2022)
Flowering time is strongly related to the environment, while the genotype by environment interaction study for flowering time is lacking in Brassica napus (B. napus). Here, a total of 11,700,689 single nucleotide polymorphisms in 490 B. napus accessions were used to associate with the flowering time and related climatic index in eight environments using a compressed variance-component mixed model, 3VmrMLM. As a result, 19 stable main-effect quantitative trait nucleotides (QTNs) and 32 QTN-by-environment interactions (QEIs) for flowering time were detected. Four windows of daily average temperature and precipitation were found be climatic factors highly correlated with flowering time. Ten main-effect QTNs were found to be associated to these flowering time-related climatic indexes. Using differentially expressed gene (DEG) analysis in semi-winter and spring oilseed rapes, 5,850 and 5,511 DEGs were found to be significantly expressed before and after vernalization. Twelve and fourteen DEGs, including 7 and 9 known homologs in Arabidopsis, were found to be candidate genes for stable QTNs and QEIs for flowering time, respectively. Five DEGs were found to be candidate genes for main-effect QTNs for flowering time-related climatic index. These candidate genes, such as BnaFLCs, BnaFTs, BnaA02.VIN3, and BnaC09.PRR7, were further validated by the haplotype, selective sweep, and co-expression networks analysis. The candidate genes identified in this study will be helpful to breed B. napus varieties adapted to particular environments with optimized flowering time.